University‐industry collaboration in project‐based learning: Perspective and motivation of industry partners - PAN, Gary (Institutional Knowledge at Singapore Management University, 2023)
Extant research has examined the essence of university-industry partnership from the university’s perspective. However, little is known about managing such partnership from an industry partner’s perspective. Understanding industry partner’s perspective is important as it may help the university to better manage the collaboration process, while keeping the focus on providing students with a positive project-based learning (PBL) experience. This study surveyed 33 industry partners to examine university-industry partnerships in a PBL setting from an industry partner’s perspective. The results show that project output needs to cater to the actual need, requirement, and expectation of the industry partner. Also, there must be efficient communication between industry partners, academics, and students for the collaboration to be successful. By understanding how to manage such university-industry partnership from the perspectives of industry partners, it would help universities to improve the PBL pedagogy in their curriculum. Also, companies may learn to better work with students and academics to generate new ideas that address their existing problems and issues.